Effects of duodenal–jejunal bypass surgery in ameliorating nonalcoholic steatohepatitis in diet-induced obese rats - Yu HH (Dove Medical Press, 2019)
Hsin-Hsien Yu,1–3 Mao-Chih Hsieh,2,3 Szu-Yuan Wu,4,5 Edgar D Sy,6 Yan-Shen Shan1,6 1Institute of Clinical Medicine, College of Medicine, National Cheng Kung University, Tainan, Taiwan; 2Division of General Surgery, Department of Surgery, Wan Fang Hospital, Taipei Medical University, Taipei, Taiwan; 3Department of Surgery, School of Medicine, College of Medicine, Taipei Medical University, Taipei, Taiwan; 4Department of Radiation Oncology, Wan Fang Hospital, Taipei Medical University, Taipei, Taiwan; 5Department of Internal Medicine, School of Medicine, College of Medicine, Taipei Medical University, Taipei, Taiwan; 6Department of Surgery, National Cheng Kung University Hospital, College of Medicine, National Cheng Kung University, Tainan, Taiwan Background: Duodenal–jejunal bypass (DJB) is an important component of many types of current bariatric surgery including Roux-en-Y gastric bypass, mini-gastric bypass, biliopancreatic diversion, duodenal switch, and DJB plus sleeve gastrectomy. Surgery is often observed to ameliorate nonalcoholic steatohepatitis (NASH), but without a clearly delineated mechanism. In this study, we investigated the effects of DJB in diet-induced obese rats with NASH. Materials and methods: Male Wistar rats were divided into four groups and fed the following diets over 6 months: A) normal chow (NC group, n=6); B) methionine–choline-deficient (MCD)–high-fat (HF) diet (HF group, n=6); C) MCD–HF diet for 3 months followed by DJB and MCD–HF diet for subsequent 3 months (DJB group, n=6); and D) MCD–HF diet for 3 months followed by treatment with pioglitazone (PGZ) with MCD–HF diet for subsequent 3 months (PGZ group, n=6). Body weight, glucose tolerance, the homeostatic model assessment-insulin resistance index, and lipid profiles were compared. Liver and visceral adipose tissue histology, inflammatory marker and hepatic stellate cell (HSC) activity, and hepatocyte autophagy were assessed. Results: Compared with the HF group, the DJB group showed improved body weight, insulin sensitivity, lipid metabolism, and steatosis severity. The DJB group exhibited a significantly lower nonalcoholic fatty liver disease activity score than the HF and PGZ group (P<0.001 and P=0.003, respectively). Furthermore, DJB significantly reduced fat mass and adipocyte size. These effects were also observed in the PGZ group. Therefore, we speculated that the improvements induced by DJB are closely related to an alteration in insulin sensitivity. Moreover, DJB HSC activity and TNF-α expression and enhanced hepatocyte autophagy. Conclusion: DJB improves NASH through several mechanisms, particularly by altering insulin sensitivity, inflammatory responses, HSC activity, and hepatocyte autophagy. Keywords: duodenal–jejunal bypass, nonalcoholic steatohepatitis, insulin sensitivity, hepatic stellate cell activity, hepatocyte autophagy